An NBS-LRR-encoding gene CsRPM1 confers resistance to the fungus Colletotrichum camelliae in tea plant - Wuyun Lv; Yingjie Xu; Hong Jiang; Qinghai Cao; Xinchao Wang; Yuchun Wang (Beverage Plant Research)
Nucleotide binding site, leucine-rich repeat (NBS-LRR) proteins are the main types of disease resistance proteins in plants, which can perceive plant pathogens. Anthracnose, caused by the fungus Colletotrichum camelliae, is one of the most severe diseases in tea plant. Here, we identified an NBS-LRR-encoding gene, CsRPM1, probably conferring resistance of tea plant to C. camelliae. Phylogenetic analysis showed that CsRPM1 was clustered with RPM1 in Arabidopsis and grouped into CC-NBS-LRR (CNL). It contained a signal peptide, a NB-ARC domain, and multiple LRR motifs. RNA-seq and qRT-PCR analysis showed that the transcript level of CsRPM1 was significantly up-regulated after inoculation with C. camelliae. Transiently silencing of CsRPM1 in tea leaves comprised the resistance to C. camelliae, indicating that CsRPM1 was required for plant defense against the pathogen. The subcellular localization showed that CsRPM1 protein was localized in the nucleus, cytoplasm, and cell membrane. Furthermore, the promoter region of CsRPM1 gene contained MeJA-responsive elements, and the expression of CsRPM1 was induced by exogenous methyl jasmonate, suggesting that CsRPM1 gene may be closely related to JA signaling pathway. A total of 17 transcription factors might be responsible for the expression of CsRPM1. Our data indicates that CsRPM1 is required for disease resistance to C. camelliae in tea plant. The characterization of this disease resistance gene sheds light on NLR protein function in tea plant and may facilitate breeding to control the severe anthracnose.